The muscular flexibility training and the range of movement improvement: a critical literature review - Luís Filipe dos Santos Coelho (Motricidade, 2007)
The muscular flexibility training put in evidence a train of neurophysiological principals and an intricate amount of muscular and viscous-elastic properties. There are a lot of stretching methods, used on the clinical and sport contexts. Despite its common utilization, it isn’t usual the health and educational professionals reflect about the compounds and efficacy of the diverse stretching methods. In this article, we realize a critical review about the diverse methods used on the flexibility training, as the principles and parameters related with that. We will done special emphasis to the principles of the proprioceptive neuromuscular facilitation and the diverse local relaxation methods, like warming. We will also have in count the revealing data relating to the Elasticity Coefficient paradox, witch can help to conceive an intervention philosophy of the flexibility training different from what it have being defended and practiced.